Cytomegalovirus Enteritis Causing Ileal Perforation in an Elderly Immunocompetent Individual - Cha, Jae Myung (Yonsei University College of Medicine, 2010)
Cytomegalovirus (CMV) infection is usually subclinical in immunocompetent individuals, however it can be life threatening in an elderly immunocompetent individual. We report a case of CMV enteritis causing ileal perforation in a physically active elderly man. An 88-year-old healthy man presented with abdominal pain and diarrhea. After initial conservative treatment, emergency laparotomy was performed for ileal perforation. The diagnosis of CMV enteritis was based on histological findings revealing many large cells with CMV inclusion bodies in the surgical specimen. In elderly individuals, even though they are immunocompetent, CMV enteritis may result in major complications such as bowel perforation, and it should be included in the differential diagnosis of diarrhea if it is resistant to conventional treatment.